Analisis Model Cooperative Learning Tipe TGT dan STAD dalam Pembelajaran: Studi Literatur - Nur Hasanah; Linggaria Lova; Imam Syafe’i; Eti Hadiati; Ratu Vina Rahmatika (STIT Ahlussunnah Bukittinggi, 2026)
Cooperative learning models such as Teams Games Tournament (TGT) and Student Teams Achievement Division (STAD) are approaches that focus on group collaboration, active student engagement, and improved academic achievement. The purpose of this study is to explain the concepts, characteristics, implementation steps, as well as the advantages and disadvantages of the TGT and STAD cooperative learning models in learning activities. The methodology used in this study is a literature review, examining various academic sources including national journals, books, research articles, and other references related to TGT and STAD cooperative learning. Data collection was conducted through documentation and content analysis of the referenced literature. The findings of this study indicate that the TGT model has a key distinguishing feature, namely the use of academic games and tournaments, which can enhance learning motivation, engagement, social interaction, and create a pleasant learning atmosphere. On the other hand, the STAD model places greater emphasis on teamwork, individual responsibility, personal quizzes, and group rewards, making it effective in improving students’ conceptual understanding, learning outcomes, and collaborative skills. Both models have proven effective in improving the quality of learning, as they encourage students to be more active, communicative, and collaborative. However, implementing these models requires effective classroom management, thorough teacher preparation, and sufficient time allocation to ensure that the learning process runs optimally. Therefore, the TGT and STAD cooperative learning models can serve as innovative strategies for improving the quality of education at various levels of learning.